Analysis of criminal law on ecocide: A case study of war in Ukraine - Haltsova, Viktoriia V. (2024)
While actions leading to environmental degradation already have global consequences threatening the very existence of humanity, the war in Ukraine has once again proved the effectiveness of existing international environmental protection mechanisms. The purpose of this study is to analyze existing international environmental protection mechanisms from the perspective of the possibility of criminalizing the crime of ecocide. Based on the analysis of the domestic law of countries that have incorporated ecocide as a crime, it follows that national approaches to addressing this issue depend on historical conditions and have significant differences. These differences hinder the prosecution of ecocide in the absence of appropriate international legal mechanisms, while the consequences of ecocide cause global damage. An analysis of the state of international regulations has shown that despite the existence of an extensive environmental protection mechanism, it remains imperfect, thus making it impossible to prosecute ecocide unless it is done in connection with war crimes. An assessment of the data presented in the reports on the war in Ukraine shows that participation in relevant international conventions does not in any way guarantee that the aggressor country will not violate its international obligations. It is shown that recognizing ecocide as a crime at the international level remains the only effective means to bring perpetrators to justice. The results of the study can be used to further improve the legal mechanisms for prosecuting ecocide, in teaching legal disciplines, and in further academic research.